Migrations And Human Development In Southern Africa: The Controversy About Freedom Of Movement For Workers In The Region - Bidaurrazaga Aurre, Eduardo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The proliferation during recent decades of regional integration projects in various parts of the world has led to processes of liberalization among the participant economies, mainly focussing on the markets for goods and services and capital, usually not including an expansion of intraregional freedom of movement for workers. In the case of Southern Africa, following renewed momentum in the construction of the SADC (Southern African Development Community), free movement of labour in a region with a strong migratory tradition has become a question of fierce controversy, mainly due to the opposition to it shown by the SADC’s economically most advanced countries, especially South Africa, the main destination of the migration flows from neighbouring countries. This article explores this controversial issue and assesses the impact of those measures so far implemented on the development perspectives of the region as a whole.
Keywords: labour freedom of movement; SADC; restrictions; south africa; conflicts